Penggunaan Amonium Hidroksida Pada Pencelupan Benang Wol Dengan Zat Warna Reaktif - Fenny Nurherawati (Universitas Insan Cendekia Mandiri, 2020)
Dyeingof wool yarn with reactive dyes is affected byfixation process with ammonium hydroxide, because it can produce good color fastness properties. The purpose of this study was to determine the effect of fixation process on wool yarn dyeing usingexhaust method withreactive dyes (Lanasol Red B), by experimenting with varying ammonium hydroxide concentrations of 3%, 4%, 5% and 6% and fixation time of 10, 20, 30 and 40 minutes. Tests carried out on color strength, colorfastness torubbing, colorfastness towashing and tensile strength of wool yarn. The resultsof experiments and tests show that the higher the use of ammonium hydroxide concentrations up to 5% and the fixation time of 20 minutes, the color strength, color fastness to rubbing and color fastness to washing increase, but using higher ammonium hydroxide concentrations and fixation time caused color strength,color fastness to rubbing, color fastness towashing and the tensile strength of wool yarnvalues relatively decreased.